Satisfacción del usuario interno y calidad de atención de salud en el control prevacacional Hospital Rebagliati 2008 - Gutierrez Flores, Evelia Flavia (2011)
The sanitary services are of quality when they lack defficiency and they satisfy the internal and external user's necessities; it is determined by conditions of the user's satisfaction, like they are: justness, reliability, effectiveness, good treatment, respect, information, continuity and confort. This study was carried out in the Hospital Edgardo Rebagliati Martins with the internal users that went to its control prevacational in the unit of Occupational Health, during the months of March to May of the year 2008. General Objective: To determine the existent relationship between the internal user's satisfaction and the quality of attention of health in the control prevocational of the Hospital Edgardo Rebagliati Martins of EsSalud. Material and method: I study descriptive, traverse, where the population in study was constituted by all the programmed workers of health that they go to carry out her control pre vacational in the unit of occupational health of the Hospital Edgardo Rebagliati Martins. The sample belonged to 285 internal users. The used method was the survey, as technique the interview, was used like instrument a structured questionnaire elaborated specifically by the author for the investigation divides in 2 parts: Quality of attention with 8 dimensions and Satisfaction of the User with 9 dimensions. Results: The level of the internal user's satisfaction assisted in the control prevacational is of 18%, while the dissatisfaction is given by 82%. The Quality of Attention of health in the Control prevocational is to regulate with 52% and bad with 48%. The quality of attention and the user's satisfaction have a highly significant ( 2 = 56.131, p < 0.01 and r=0 .823) relationship. Conclusions: The weaknesses that the internal users perceived: time of wait prolonged to receive attention, insufficient number of personal and the strengths that you/they manifested good treatment on the part of the doctor and of the infirmary personnel, as well as privacy and trust, among other. To establish the mensuration of the user's satisfaction and the quality of attention this method it is assertive, it is the first time that is carried out a study of this nature in the Unit of occupational Health.